1989
DOI: 10.1016/0741-5214(89)90475-8
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced platelet activation: The role of thromboxane A2 synthesis and the extent of platelet granule release in two patients

Abstract: Heparin-induced thrombosis is due to an immune-mediated activation of circulating platelets and has significant clinical implications for patients with vascular disease. The purpose of this article was (1) to define the biochemical mechanisms of heparin-induced platelet activation (HIPA) and (2) to determine the relationship between thromboxane A2 (TxA2) synthesis and platelet granule release. In two patients with confirmed HIPA, heparin (3 U/ml) induced extensive platelet aggregation (61.5%), release of 14C-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In this study, heparin resulted in P-selectin expression, dense granule release and microparticle formation from donor platelets in the presence of plasma from patients with HIT. These results confirm previous studies in which platelet granule release by HIT-associated immunoglobulin and heparin and platelet-derived microparticle formation have been observed (9,22,23). In this study, heparin resulted in a slight increase in aggregation and P-selectin expression in control samples, confirming the direct platelet-activating effects of heparin (22).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, heparin resulted in P-selectin expression, dense granule release and microparticle formation from donor platelets in the presence of plasma from patients with HIT. These results confirm previous studies in which platelet granule release by HIT-associated immunoglobulin and heparin and platelet-derived microparticle formation have been observed (9,22,23). In this study, heparin resulted in a slight increase in aggregation and P-selectin expression in control samples, confirming the direct platelet-activating effects of heparin (22).…”
Section: Discussionsupporting
confidence: 93%
“…These authors showed that serum and purified IgG from two patients with HIT induced aggregation of normal plate lets in the presence of therapeutic concentrations of heparin. That hepa rin-dependent antibodies are potent platelet activators was confirmed by several authors and it was shown that these antibodies also cause thromboxane A2 generation and platelet granule release (35)(36)(37)(38). This last property formed the basis for the development of a sensitive and specific method for the laboratory diagnosis of heparin-dependent anti bodies (39).…”
Section: Pathophysiology Of Heparin-induced Thrombocytopeniamentioning
confidence: 81%
“…Based on the fundamental in vitro and in vivo experiments, antiplatelet drugs might prevent the occurrence of HIT [38], [39]; by contrast, several clinical trials have confirmed that antiplatelet drugs do not effectively suppress the occurrence of HIT [40], and antiplatelet drugs do not reduce the occurrence and degree of thrombocytopenia [41]. However, these studies were limited to case reports or research using a small sample size.…”
Section: Discussionmentioning
confidence: 99%